Tunneling Negative Magnetoresistance via δ Doping in a Graphene-Based Magnetic Tunnel Junction - 袁建辉 陈妮 莫华 张燕 张志海 (Chinese physics letters, 2016)
We investigate the tunneling magnetoresistance via δ doping in a graphei2e-based magnetic tunnel junction in detail. It is found that the transmission probability and the conductance oscillates with the position and the aptitude of the 8 doping. Also, both the transmission probability and the conductance at the paxallel configuration are suppressed by the magnetic field more obviously than that at the antiparallel configuration, which implies a large negative magnetoresistance for this device. The results show that the negative magnetoresistance of over 300% at B = 1.0 T is observed by choosing suitable doped parameters, and the temperature plays an important role in the magnetoresistance. Thus it is possible to open a way to effectively manipulate the magnetoresistance devices, and to make a type of magnetoresistance device by controlling the structural parameter of the δ doping.